2019
DOI: 10.1093/mnras/stz1538
|View full text |Cite
|
Sign up to set email alerts
|

Photometry and colour index of Comet 67P/Churyumov-Gerasimenko on 2015 December 12

Abstract: Comet 67P/Churyumov-Gerasimenko (hereafter, 67P) was observed on 12 December 2015, from 2 m Himalayan Chandra Telescope in India in photometry to study its dust properties, using Bessell R and I filters. We study the photometric images to highlight coma structures and jets. The radial decrease in intensity in the different coma structures are compared to the azimuthally integrated intensities. The observations of the slopes show a quasi-steady-state coma to an optocentric distance of about 20 000 km. The chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We note that the dust of 46P/Wirtanen appears somewhat bluer than that of Comet 67P/Churyumov-Gerasimenko at a small phase angles. Using the Bessel R and I filters, Sen et al (2019) reported S' = (21.5 ± 6) % per 0.1 μm in Comet 67P/Churyumov-Gerasimenko; whereas, with a similar pair of filters we found a colour slope of 46P/Wirtanen to be either about zero or slightly negative. We did use a somewhat smaller aperture, 5000 km versus 11,000 km of Sen et al (2019).…”
Section: Colour Of the Inner Coma In Comet 46p/wirtanenmentioning
confidence: 60%
See 2 more Smart Citations
“…We note that the dust of 46P/Wirtanen appears somewhat bluer than that of Comet 67P/Churyumov-Gerasimenko at a small phase angles. Using the Bessel R and I filters, Sen et al (2019) reported S' = (21.5 ± 6) % per 0.1 μm in Comet 67P/Churyumov-Gerasimenko; whereas, with a similar pair of filters we found a colour slope of 46P/Wirtanen to be either about zero or slightly negative. We did use a somewhat smaller aperture, 5000 km versus 11,000 km of Sen et al (2019).…”
Section: Colour Of the Inner Coma In Comet 46p/wirtanenmentioning
confidence: 60%
“…Using the Bessel R and I filters, Sen et al (2019) reported S' = (21.5 ± 6) % per 0.1 μm in Comet 67P/Churyumov-Gerasimenko; whereas, with a similar pair of filters we found a colour slope of 46P/Wirtanen to be either about zero or slightly negative. We did use a somewhat smaller aperture, 5000 km versus 11,000 km of Sen et al (2019). It also is worth noting that colour imaging revealed a decrease of reddening in the inner coma of 67P/Churyumov-Gerasimenko (see Fig.…”
Section: Colour Of the Inner Coma In Comet 46p/wirtanenmentioning
confidence: 60%
See 1 more Smart Citation